Assimilation of nitrogen and carbon isotopes from fish diets to otoliths as measured by nanoscale secondary ion mass spectrometry. (21st June 2018) - Shiao, Jen‐Chieh; Shirai, Kotaro; Tanaka, Kentaro; Takahata, Naoto; Sano, Yuji; Sung‐Yun Hsiao, Silver; Lee, Der‐Chuen; Tseng, Yung‐Che
Abstract : RATIONALE: Nitrogen and carbon stable isotope ratios (δ 15 N and δ 13 C values) of carbonate‐bound organic materials in otoliths can provide information to address the biological and ecological functions of fish. Correct interpretation of otolith δ 15 N and δ 13 C profiles requires knowledge of the metabolic routes of nitrogen and carbon isotopes. However, the isotopic assimilation of δ 15 N and δ 13 C compositions from diets to otoliths has rarely been investigated. METHODS: This study traced the daily nitrogen and carbon isotopic assimilation between diets and otoliths using nanoscale secondary ion mass spectrometry (NanoSIMS). Isotopically labeled algae ( Tetraselmis chui ) were fed to tilapia ( Oreochromis niloticus ) for 14–17 days. NanoSIMS and conventional isotope ratio mass spectrometry were used to measure δ 15 N and δ 13 C variations in the otoliths and fish muscle, respectively. RESULTS: Otolith δ 15 N values abruptly surged from natural abundance levels by 1000–2300‰ after the fish ate 15 N‐spiked algae with δ 15 N values of approximately 2200‰. However, the δ 15 N values of fish muscle increased to only approximately 500‰ at the end of the feeding experiment. Much higher δ 15 N values (3700–14 000‰) and moderate δ 13 C values (60–200‰) were detected in the otoliths after the tilapia ate 15 N‐ and 13 C‐spiked algae with a δ 15 N value of 36667‰ and a δ 13 C value of 272‰. Mapping analysis showed sub‐micrometer‐scale distribution of 15 N embedded in the otolith growth increments with a low‐to‐high δ 15 N signal after the tilapia shifted diets from non‐spiked to 15 N‐labeled algae. CONCLUSIONS: These results suggest that otolith nitrogen and carbon isotopes from food were directly assimilated on the same day. Food is the major and in some cases only source of otolith nitrogen isotopes but makes only a partial contribution to otolith carbon isotopes. Therefore, the δ 15 N values recorded in the sclerochronological layers of the otoliths can be used to determine the trophic levels, food sources and diet changes of fish.